2020
DOI: 10.2478/msp-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

DC electrical conduction in strontium vanadium borate glasses

Abstract: A series of borate glasses with the composition x(SrO) · (50 – x)V2O5 ·0.5(B2O3) where x = 0, 0.1, 0.2, 0.3 and 0.4 were prepared by melt-quenching technique. The non-crystalline nature of the glasses has been established by XRD studies. Room temperature density and DC electrical conductivity of the samples were investigated in the temperature range of 300 K to 443 K. The molar volume and oxygen packing density (OPD) were estimated. The results show that the density, molar volume and OPD decrease with the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The AC conductivity has not been studied. Arunkumar V. Banagar, et al (2020) (11) , have reported the DC conductivity of strontium vanadium borate glasses by varying V 2 O 5 . The frequency variation with conductivity has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The AC conductivity has not been studied. Arunkumar V. Banagar, et al (2020) (11) , have reported the DC conductivity of strontium vanadium borate glasses by varying V 2 O 5 . The frequency variation with conductivity has not been investigated.…”
Section: Introductionmentioning
confidence: 99%